MENINGKATKAN PENDAPATAN DAN PEMENUHAN PANGAN MANDIRI DESA SUMBERREJA MELALUI AKUAPONIK - Giffari, Muhamad Syafiq; Ekasari, Agustina; Rahmawati, Rafika (Universitas Islam 45 Bekasi, 2023)
This community service activity aims to provide outreach and education regarding the application of aquaponics and cultivating catfish using materials available in the environment to the people of Sumbereja Village, Pebayuran District, Bekasi Regency. The majority of residents in this village are farmers and livestock breeders, so the implementation of aquaponics is expected to increase economic income and meet household needs. Aquaponics is an agricultural system that combines the cultivation of fish and vegetable plants by using fish waste as nutrients for plants. This system also functions as a dirt filter, maintaining water quality. Catfish were chosen as cultivated fish because they have high nutritional value. Apart from that, catfish is also suitable for consumption by various age groups. This activity involves socialization, making simple aquaponics, and practical training. As a result, participants became more aware of waste management and aquaponic technology. They are also enthusiastic about applying it in their homes. During the evaluation, some participants were even interested in trying to make liquid organic fertilizer from dry leaf waste and household waste. It is hoped that this activity can continue to be developed to increase residents' ability to utilize the resources around them, as well as improve environmental conditions and increase family income.